E-Modul with Integrated PDEODE Strategy Islamic Values Based on Book Creator: E-Modul dengan Strategi PDEODE Terintegrasi Nilai-Nilai Islam Berbasis Book Creator - Sepriraningrum, Sepriraningrum; Robia Astuti; Istiani, Ana (Halaqa: Islamic Education Journal, 2024)
E-module with PDEODE strategy Integrated Islamic values based on Book Creator is a learning innovation that combines Project-based approach with PDEODE strategy. E-modules with PDEODE strategy integrated with Islamic values based on Book Creator aim to improve learning effectiveness. The PDEODE strategy emphasizes students to play an active role during the learning process, thinking logically and theoretically based on balance. The purpose of this research is to produce a feasible and effective Book Creator on SPLDV material. The research method used is research and development by adopting 4-D steps, namely define, design, develop, and disseminate. The data collection techniques used are expert assessment, questionnaires and learning outcomes tests. The data analysis technique used is the feasibility test based on expert judgment, and the effectiveness test based on user responses, and learning outcomes. The results showed that the e-module media based on expert assessment received an average score of 4.6 which means that the e-module learning media is feasible to use. While the results of data analysis from the e-module media effectiveness test based on student responses obtained a score of 92.70% who responded positively, and student learning outcomes obtained a classical completeness score of 85.18%, this shows that the e-module is effective to use. Thus it can be concluded that the e-module is declared feasible and effective.